The Upper Pleistocene stratigraphy of the Starunya site as a “bridge” between the stratigraphical frameworks of Western Europe and the plain area of Ukraine - Adamenko O.M. (Днепропетровский национальный университет им. Олеся Гончара, 2019)
The first discoveries of mummified carcasses of the woolly rhinoceros, mammoth, horse, roe deer and other animals were made at a depth of 12 m in the course of mining work at an ozokerite mine near the village of the Starunia. In 1929 an expedition of the Academy of Arts and Sciences from Krakow, when investigating the mine at a depth of 17 m, found the remains of 3 more woolly rhinoceroses. There were also numerous bones of small vertebrates (rodents), artichokes, numerous insects, beetles, parasitic worms, fleas, butterflies, spiders, snails, vascular plants, seeds and branches of dwarf birch, alder, and other representatives of tundra flora. In March 1977, after the earthquake in the Vrancha Mountains (Romania), the first and still the only mud volcano in the Carpathians, which added an entirely new “ note “ to the Starunia paleontological location , arose on the ozokerite deposit. In the 1970s-80s several dozen remains of ancient man from the late Paleolithic, Mesolithic and Neolithic periods were discovered. In 2004-2009, two Ukrainian-Polish expeditions were organized. The results of both expeditions were published in 2005 in the book «Polish and Ukrainian Geological Studies (2004-2005) at Starunia – the area of discoveries of Woolly Rhinoceros» and the scientific collection «Interdisciplinary Studies (2006-2009) at Starunia (Carpathian Region, Ukraine). The main achievements are set forth in 17 articles and relate to the geological environment, geomorphology, lithology, stratigraphy and paleography of the Holocene deposits, their palynological and paleobotanical characteristics, chronostratigraphy and environmental changes during the period of the late Pleistocene and Holocene, and also research by methods of electric probe, gravity and microgravity survey, geochemical analysis, microbiological characteristics and bitumen of Quaternary deposits. An important result was the discovery of the most productive area where the remains of giant mammals and even Pleistocene Cro-Magnon could still be found at depths. All the numerous interdisciplinary research of Polish and Ukrainian scientists confirms the uniqueness of Starunia on a global scale, requiring the preservation and further study of the paleontological finds and of the only mud volcano in the Carpathians. Such findings can only be made by organizing the Starunia International Ecological and Tourist Center «Geopark Ice Age».
Keywords: Upper Pleistocene; woolly rhinoceros; mammoth; tundra; natural-man-made geosystems; paleoclimate; верхній плейстоцен; волохатий носоріг; мамонт; тундра; природно-антропогенні геосистеми; палеоклімати; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен